2007
DOI: 10.2165/00019053-200725120-00005
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin

Abstract: Atorvastatin is a lipid-lowering agent that has been evaluated in a number of primary and secondary intervention studies. In the primary prevention trials ASCOT-LLA and CARDS, atorvastatin 10 mg/day significantly reduced cardiovascular events compared with placebo. A prospectively conducted economic analysis of the 3.3-year ASCOT-LLA trial showed that atorvastatin was associated with incremental cost-effectiveness ratios (ICERs) of euro11,693 (UK) and euro12,673 (Sweden) per event avoided (2002 values). Longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…The financial barriers identified corroborate and extend previous findings that highlight clinicians are concerned that myopia control is expensive, timely, and occupies valuable chair time 23 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The financial barriers identified corroborate and extend previous findings that highlight clinicians are concerned that myopia control is expensive, timely, and occupies valuable chair time 23 .…”
Section: Discussionsupporting
confidence: 82%
“…Clinic based optometrists identified inadequate and insufficient education and training as well as a lack of availability of myopia control therapies as a fundamental justification for their reluctance to practise myopia control. This supports the results from Wolffsohn et al's survey that revealed, amongst other barriers, a lack of availability of and information on myopia control means that the majority of international practitioners still prescribe single-vision correction as the primary mode of management for myopic patients, even in countries where the control of myopia progression has become an important clinical goal 23 . The perceived lack of availability of myopia control management options highlights the need for further education and regulatory guidance.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations